Level of protein for heifers wintered on bluestem pasture - DeGeer, C.V.; Hall, M.C.; Smith, E.F. (Kansas Agricultural Experiment Station, 2011)
The 66 heifers used were good to choice grade Herefords purchased near Fort Davis, Texas, and assigned to treatments on a random weight basis. They were rotated among pastures to minimize pasture differences during the first winter and summer. Di-calcium phosphate was fed to standardize phosphorus intake among groups during the first winter and each was fed 15,000 I.U. of Vitamin A daily. Salt was available to all lots throughout the test. They were fed three times weekly during the winter.
Keywords: Beef; Protein; Di-calcium phospate; Phosphorus